Encyclopedia of polymer blends. Volume 3, Structure - Isayev, Avraam I., 1942- (Weinheim : Wiley-VCH, 2016)
A complete and timely overview of the topic, this Encyclopedia imparts knowledge of fundamental principles and their applications for academicians, scientists and researchers, while informing engineers, industrialists and entrepreneurs of the current state of the technology and its utilization. - The most comprehensive source on polymer blends available on the market - Offers a complete and timely overview of the topic - Each article presents up to date research & development on a topic and its basic principles and applications, integrates case studies, laboratory and pilot plant experiments, and gives due reference to published and patented literature - Equips academics, scientists and researchers with knowledge of fundamentals principles and their applications, and informs the engineers, industrialists and entrepreneurs about the state of the art technology and its applications.
Glass-Transition Phenomena in Polymer Blends / Ioannis M Kalogeras -- Crystallization and Melting Behavior in Polymer Blends / Saleh A Jabarin, Kazem Majdzadeh-Ardakani, Elizabeth A Lofgren -- Morphology and Structure of Crystalline/Crystalline Polymer Blends / Zhaobin Qiu, Shouke Yan -- Rubber-Plastic Blends: Structure-Property Relationship / Sudhin Datta -- Morphology of Rubber/Rubber Blends / Avraam I Isayev, Tian Liang -- Phase Morphology and Properties of Ternary Polymer Blends / VN Kuleznev, YuP Miroshnikov -- Morphology and Structure of Polymer Blends Containing Nanofillers / Hossein Nazockdast.
Includes index.
Online resource; title from PDF title page (Wiley, viewed June 30, 2016).
Keywords: Polymers -- Mixing -- Encyclopedias; Polymers -- Mixing; SCIENCE / Chemistry / Physical & Theoretical; Electronic books; Encyclopedias